Islam, Christianity and tradition : a comparative exploration - Netton, Ian Richard (Edinburgh University Press, 2006)
A unique comparative exploration of the role of tradition in Islam and Christianity. The idea of 'tradition' has enjoyed a variety of senses and definitions in Islam and Christianity, but both have cleaved at certain times to a supposedly 'golden age' of tradition from the past. Key Themes The roles of authority Fundamentalism The use of reason Ijtihad (independent thinking) Original comparisons between Islamic Salafism and Christian Lefebvrism Ian Richard Netton suggests there has been a chain of thinkers from classical Islam to the 20th century who share a common interest in ijtihad (or independent thinking). Drawing on past and present evidence, and using Christian tradition as a focus for contrast and comparison, he highlights the seemingly paradoxical harmony between tradition and itjihad in Islam. By using a variety of primary and secondary sources including contemporary newspaper and journal articles, documents and letters, he adds an immediacy to this lucid and stimulating text. Key Features Proposes a new vocabulary for the articulation of Islam Offers original comparisons between Salafism and Lefebvrism Highlights the paradoxical harmony between tradition and itjihad in Islam Articulates the yearning amongst today's Muslim and Christian traditionalists for a revival of a 'golden age' from whence, they believe, all good traditions derive